Study on The Ability of H2O2 and The Effective Concentration of CuSO4 in Degrading Cyanide - Niati, Sri Murda; Lukman, Lukman; Supraptiah, Endang; Cahya, Gemala (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2023)
PT. Aneka Tambang conducts gold processing using NaCN reagents, then from the gold processing process produces waste containing cyanide which can cause damage to the environment. One method used to reduce cyanide concentrations is the Degussa method. The Degussa method is a method to degrade free cyanide in waste by using H2O2 and Cu2+ ions as a catalyst source so that it becomes a harmless cyanide compound (cyanate ion). The purpose of the study was to determine the ability of hydrogen peroxide and determine the effective concentration of copper sulfate in degrading cyanide in the Degussa process and determine the level of stability of hydrogen peroxide oxidizers in the open air. Sample testing was carried out by varying the H2O2 retrieval time, variations in H2O2 dilution factor and copper sulfate concentration variations, then the sample was stirred with a jartes stirrer for 15 minutes. Cyanide is determined by spectrophotometer, the absorbance obtained is fed into the linear regression equation so that the final free cyanide concentration is obtained. From the experiment, it can be concluded that the concentration of cyanide degradation is effectively obtained when hydrogen peroxide and copper sulfate that have been mixed in the mixing tank are right out of use.